A Review of State-Level Procedural Guidance for Implementing Multitiered Systems of Support for Behavior (MTSS-B). (July 2020) - Briesch, Amy M.; Chafouleas, Sandra M.; Nissen, Kristin; Long, Stephanie
Given the authority of state government over public education, one means of narrowing the best-practice to actual-practice gap in education is by putting forth clear state guidance and recommendations to schools. To date, however, little is known about the national landscape of procedural guidance that is readily available to practitioners looking to implement multitiered systems of support for behavior (MTSS-B). The purpose of the current study was to conduct a systematic review of state department of education websites to understand what guidance is afforded to local education agencies regarding MTSS-B. Results supported that roughly half of the states provided some form of procedural guidance for MTSS-B; however, both the type (e.g., what interventions to use, how often to progress monitor) and level of guidance varied widely. When states did provide behavior-specific guidance, documents were most likely to include specification of what types of interventions and measures to utilize; information less typically focused on assessment such as indications as to how often data should be collected and reviewed or what decision rule(s) should be used to determine student responsiveness. Implications for local implementation and strengthening future state-level guidance for MTSS-B are discussed.